PENERAPAN METODE DISKUSI KELOMPOK KECIL PADA MATERI MENENTUKAN IDE POKOK TEKS BACAAN DI KELAS V SDN 1 TEPUNG SARI - Wahid, M Nurrohman; Kusuma, Mega; Hetilaniar (STKIP Subang, 2026)
This research is based on the reality of fifth-grade students at SDN 1 Tepung Sari, where students' literacy skills in determining main ideas are still concerning. Students tend to get stuck in the pattern of copying the first sentence of a paragraph without truly analyzing the essence of the reading. To overcome this impasse, this study implemented the Small Group Discussion method. Through a Classroom Action Research (CAR) approach over two cycles, a significant transformation in the learning atmosphere was found. The results showed that a more intimate and non-intimidating discussion space allowed students to exchange strategies for understanding texts collegially. Quantitatively, there was a surge in classical completion rates from only 40% in the pre-cycle to 90% at the end of the second cycle. This study concludes that shifting problem-solving authority from teachers to students through small groups not only improves academic scores but also fosters students' critical thinking in analyzing reading texts.